Do the unemployed hit the bottle during economic downturns? An empirical approach for Spain - Carla Blázquez-Fernández; David Cantarero-Prieto; Patricio Perez (BMC, 2019)
Abstract Background This paper analyses the 2008 economic collapse in Spain with its long-lasting effects. Precisely, the ones associated with lifestyles. Thus, the aim of this paper is to examine to what extent economic downturns affect individual's drinking behavior when focusing on unemployed people. Methods We use discrete-choice models and matching techniques. Data from the National Health Survey for 2006 and 2011-2012 provides a clear picture before and after the 2008 breakdown in Spain. Results We find that drinking over the business cycle is a function of individual socio-demographic status. Besides, our empirical findings are consistent with the idea that following the crisis differences between unemployed and non-unemployed fell to at least in accordance with a lower overall consumption of alcoholic beverages. Conclusions Public policy design for drinkers would require both prevention and recovery from alcohol use strategies to be met towards health and labour pillars.